RESPON ZAT PENGATUR TUMBUH (ZPT) DAN TINGKAT KEMATANGAN BUAH KAKAO TERHADAP MUTU FISIOLOGIS BENIH KAKAO (Theobroma cacao L.) - Bolong, Aprianto; Mahfudz, Mahfudz; Maemunah, Maemunah; Rauf, Abd.; Syamsiar, Syamsiar (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
The research aims to obtain the type of growth regulator that provides the best physiological quality for cacao seeds. To obtain a level of maturity that provides the best physiological quality of cacao seeds. carried out at the Seed Technology Laboratory, Faculty of Agriculture, Tadulako University. The research period started from February to March 2024. This research was structured using a Randomized Block Design consisting of two factors. The first factor consisted of 3 levels of treatment, namely Control (without ZPT), Young Coconut Water and ZPT Cytokinin benzyl adenine, with 3 levels Treatment: Control (without ZPT), young coconut water 50%, PGR Cytoconine benzyl adenine 30%, The second factor is the maturity level of cacao seeds consisting of 3 levels namely, yellow in the groove of the fruit, yellow in the groove and back of the fruit, yellow in all parts of the fruit. The research results showed that the interaction of growth regulators and the level of maturity of the cacao fruit had an effect on the speed of germination. The use of growth regulators in the form of cytokinin 30% benzyl adenine improves the physiological quality of cocoa seeds. The level of maturity of cocoa pods has a positive impact on the physiological quality of cacao seeds